PkM di UMKM Aulya Snack Melalui Desain Ulang Hand Sealer - Ma'muriyah, Ni'matul (Lembaga Penelitian dan Pengabdian Kepada Masyarakat Universitas Internasional Batam, 2019)
Aulya Snack is Micro Small and Medium Enterprises (UMKM), that produce traditional snacks such as Rempeyek, Kuping Gajah, and Crackers. This enterprise founded by Mrs. Rita, and located on Tiban Lama, Batam. The observation was done on October 10th until November 23th, 2016. Base on the observation, Aulya Snack has a problem with the Hand Sealer which use to seal the product packaging. They use varies types of packaging from 10x20cm (250gr) to 35x50cm (5kg), to accommodates the sealing process for their product they use two types of hand sealers, small for small packaging (250 gr to 2kg) and Big for big size packaging (3kg to 5kg). By using two types of sealer lead them to more consumption of electricity. And another problem was the handle of hand sealers that they used has difficulty to do sealing for certain size. To solve their problems we proposed a new hand sealer that can use for varies types of packaging of traditional snacks, we redesign the body of hand sealer by setting a stopper which can be moved forward and backward due to adjustment with the type of packaging. And redesign the handler of the hand sealer also. The result of the experiment showed the new sealer can sealing for all sizes that have used, and save the consumed of their electricity almost Rp. 77.778 ,-  per month.